Pengaruh Kualitas Kerja, Pengawasan dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Puskesmas Bandar Jaya Lahat (Ekonomika, 2022)
The purpose of this study is to determine the effect of work quality, supervision and work discipline on employee performance at Bandar Jaya Lahat Health Center, either partially or simultaneously. The sample in this study were all employees of the Bandar Jaya Lahat Health Center, totaling 53 people. Then the method of determining the sample in this study using the census method. The census method is a method by collecting data on the total population. Testing the effect of Work Quality (X1) on Performance (Y), obtained a Significant value, 0.014 <0.05, then accept Ha and reject Ho, which means Work Quality (X1) has a significant effect on Performance (Y). Testing the effect of Supervision (X2) on Performance (Y), obtained a Significant value, 0.000 <0.05, then accept Ha and reject Ho, which means that Supervision (X2) has a significant effect on Performance (Y). Testing the effect of Work Discipline (X3) on the Performance variable (Y), obtained a Significant value, 0.000 <0.05, then accepting Ha and rejecting Ho, which means that Work Discipline (X3) has a significant effect on Performance (Y). The calculation results obtained a Significant value of 0.000 <0.05, thus Ha is accepted and Ho is rejected, which means that Quality of Work (X1), Supervision (X2), and Work Discipline (X3) have a significant effect on performance (Y)